Pengaruh Kepemilikan Managerial, Leverage, Financial Distress Dan Kepemilikan Publik Terhadap Konservatisme Akuntansi: Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2014 - Viola, Viola; Diana, Patricia (Universitas Multimedia Nusantara, 2016)
The objective of this research is to obtain empirical evidence about the effect of managerial ownership, leverage, financial distress, and public ownership towards accounting conservatism. Accounting conservatism is important to known by management and shareholders because it indicates the financial performance of company. Sample in this research was selected by using purposive sampling method and the secondary data used in this research was analyzed by using multiple regression method. The samples in this research are manufacturing companies registered as basic and chemical industries, miscellaneous sector industry, and the consumer goods sector industry in BEI for the year 2012-2014 consecutively, published their financial reports ended in December 31 and has been audited by independent auditor, used Rupiah currency, and did not do share split. Companies that can be used as a sample were 33 firm. Results of this research was (1) managerial ownership has no significant effect towardss accounting conservatism (2) leverage has significant effect towards accounting conservatism (3) financial distress has significant effect towards accounting conservatism (4) public ownership has no significant effect towards accounting conservatism. Keywords: conservatism, financial distress, leverage, managerial ownership, public ownership.